EXPRESSIONS OF REGIONALISM IN MODERN LITHUANIAN BOOK PUBLISHING : BOOKS IN DIALECTS - Petreikis, Tomas (Knygotyra, 2016)
The development of publishing activities, focused not only on the Lithuanian literary language but also on Lithuanian dialects, testifies to the spread of values of liberal pluralism in our society, dynamics of regional information needs and spontaneously expanding self-expression fields of ethnographic communities. Modern Lithuanian dialectal publishing is an extremely fragile and poorly commercialized phenomenon of culture. So far, neither the authors nor publishers and developers of bibliographic resources have fully understood the exclusivity of a dialectal book. As a result, accounting of dialectal books has not yet been formalized; the addressee of such books has not yet been well identified; linguistic features not always established in the publication titles. A successful life of a dialectal book is closely related to the national and regional cultural policy. The maturity of regional self-awareness of communities established on the ethnographic regional level and a positive attitude of a community toward its dialect is the main driving force of dialectal publishing. The tradition of publishing dialectal books is consistently continued by the Žemaičiai (Samogitians, or Lowland Lithuanian). Their quantitative and qualitative achievements can be illustrated by the fact that in 1990–2014, 77 book titles were published in the Samogitian dialect. New traditions of publishing are being developed by the Aukštaičiai (Highland Lithuanian) – 34 titles, and the Dzūkai (12 titles), whereas the Suvalkiečiai, due to a great influence of the standard Lithuanian language, do not feel inclined to develop dialectal publishing. The ethnographic region of the so-called Mažlietuviai (from Lithuania Minor) is not numerous enough to have the capacity of developing dialectal publishing. The success of projects aimed at developing dialectal publishing can only be ensured by public organizations which act in accordance with the model of normative communities and thus engage community members into the processes of creating, publishing and disseminating the book content. Self-publishing authors usually use the services of cheap printing houses rather than show interest in developing local poligraphic industry or support local publishing companies. There are cases of successful dialectal publishing projects. However, these are more happy exceptions to the common practice. Given the situation, it is difficult to anticipate the involvement of big commercial houses in dialectal publishing. Due to the prevalence of network-based bookstores, the current system of distribution is not favourable to the dissemination of dialectal books.
Keywords: ...